Effectiveness of nutrition education in fruit and vegetable consumption in Saudi Arabia: A pre-post intervention study - Tami, Suzan H. (Edelweiss Applied Science and Technology, 2025)
Despite the well-established benefits of fruit and vegetable (FV) consumption for weight management and chronic disease prevention, intake among Saudis remains below recommended levels. This study aimed to evaluate the effectiveness of a nutrition education intervention in improving FV consumption among Saudi female college students. A pre-post intervention design guided by the logic model was employed. A total of 207 Saudi female students completed an assessment questionnaire before and after a 1.5-hour nutrition education session. The program emphasized the importance of FV consumption, provided practical strategies and recipes to increase intake, and incorporated an interactive game to promote engagement. Data were analyzed using the Wilcoxon signed-rank test. Findings: Post-intervention results indicated significant improvements in daily FV consumption (p < 0.001), awareness of personal FV intake recommendations for fruits (p < 0.001) and vegetables (p = 0.006), and the frequency of cooking vegetables at lunch (p = 0.007). Nutrition education effectively enhanced FV consumption behaviors and knowledge among participants. Implementing similar educational programs and awareness campaigns through curricula and across media platforms may help increase FV intake and promote healthier dietary habits in Saudi society.